Evaluation of Patient Satisfaction and Patient-physician Relationship in an Out- Patient Department Re-engineered through a Health Information Management System: A Descriptive Study Done at a Major Women’s Hospital in Sri Lanka - Madhuwanthi, R.M.; Marasinghe, R.B (Faculty of Allied Health Sciences University of Sri Jayewardenepura, 2021)
Introduction: Health information management is one of the major pillars in a health system that improves the effectiveness and efficiency of health services. It is essential to assess the patient perception towards re-engineered services provide through Hospital Information Management Systems (HIMSs) and how this implementation affects the doctor-patient relationship. The objective of the study was to describe the extent of patient satisfaction towards Out-Patient Department (OPD) services, pharmacy service and patient-physician relationship in the OPD, re-engineered through a HIMS, at the Castle Street Hospital for Women (CSHW), Sri Lanka. Methods: A descriptive cross-sectional study was carried out among 362 out-patients aged over 18 years attending the OPD of the CSHW during 2018-2019. Consecutive sampling method, and an interviewer-administrated questionnaire were used to collect data. The quantitative analysis was done using the SPSS software version 23. The sentiment analysis was performed to analyze comments given by patients using the Rapid Miner software. Results: All participants were females with a mean age of 41years (±13.58). Almost all participants were satisfied with overall services provided by the OPD (99.7%) and the pharmacy (98.4%). The majority (65.3%) agreed that implementation of the HIMS had improved the doctor-patient relationship. All reported comments regarding the re-engineered services of the OPD were ‘positive’. The study also suggests considering providing information in all common languages while announcing the patient’s OPD number at the waiting area in future implementations. Conclusions: The majority of patients were satisfied with the overall OPD services provided through implementation of the HIMS at the CSHW, Sri Lanka
Keywords: Health information systems, Hospital information management system, Outpatient department, Patient-physician relationship.